E-117 The influence of a carotid artery stenosis contralateral to an intracranial large vessel occlusion in mechanical thrombectomy. (22nd July 2018) - Maus, V; Borggrefe, J; Abdullayev, N; Sack, H; Psychogios, M; Mpotsaris, A; Behme, D
Abstract : Background: Clinical outcome in patients undergoing embolectomy due to intracranial large vessel occlusion is influenced by several factors. The impact of a concomitant carotid artery stenosis contralateral to the intracranial lesion remains unclear. Methods: Retrospective analysis of prospectively collected data of two comprehensive stroke centers between 2014 and 2017. Three hundred and ninety-two consecutive patients with intracranial vessel occlusion in the anterior circulation were treated with embolectomy. Clinical (including demographics and NIHSS), imaging (including angiographic evaluation of concomitant contralateral carotid stenosis), and procedural data were evaluated. Favorable clinical outcome was defined as modified Rankin Scale≤2 at 90 days. Results: In 27/392 patients (7%) pre-interventional imaging exhibited a concomitant carotid stenosis (>50%) contralateral to the intracranial lesion compared to 365 patients with a luminal reduction of ≤50%. Median admission NIHSS and procedural timings did not differ between groups. Reperfusion was successful in 303/365 (83%) vs 25/27 (93%), respectively. Median volume of the final infarct core was larger in individuals with stenosis >50% (176 (IQR 32–213) vs 11 cm 3 (1–65), p<0.0005). Rate of favorable outcome at 90 days (7% vs 35%, p<0.05) and mortality (63% vs 19%, p<0.005) differed significantly between groups. The presence of concomitant contralateral carotid stenosis in patients with intracranial vessel occlusion was associated with a poor outcome independent of age and NIHSS in multivariate logistic regression (OR 2.2 (1.1–4.7), p<0.05). Conclusion: For patients with intracranial vessel occlusion undergoing embolectomy, the presence of a contralateral carotid stenosis >50% is a predictor of poor clinical outcome. Disclosures: V. Maus: None. J. Borggrefe: None. N. Abdullayev: None. H. Sack: None. M. Psychogios: None. A. Mpotsaris: None. D. Behme: None.